Quantifying uncertainties in the solar axion flux and their impact on determining axion model parameters - Hoof, Sebastian; Jaeckel, Joerg; Thormaehlen, Lennert J. (Journal of cosmology and astroparticle physics, 2021)
We review the calculation of the solar axion flux from axion-photon and axion-electron interactions and discuss the size of various effects neglected in current calculations. For the Primakoff flux we then explicitly include the partial degeneracy of electrons. We survey the available solar models and opacity codes and develop a publicly available C/Python code to quantify the associated systematic differences and statistical uncertainties. The number of axions emitted in helioseismological solar models is systematically larger by about 5% compared to photospheric models, while the overall statistical uncertainties in solar models are typically at the percent level in both helioseismological and photospheric models. However, for specific energies, the statistical fluctuations can reach up to about 5% as well. Taking these uncertainties into account, we investigate the ability of the upcoming helioscope IAXO to discriminate KSVZ axion models. Such a discrimination is possible for a number of models, and a discovery of KSVZ axions with high E/N ratios could potentially help to solve the solar abundance problem. We discuss limitations of the axion emission calculations and identify potential improvements, which would help to determine axion model parameters more accurately.